2000
DOI: 10.1007/s004670050068
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute renal failure in newborns

Abstract: Acute renal failure (ARF) is a frequent clinical condition in neonatal intensive care units. Plasma creatinine concentrations should be used with some caution for ARF diagnosis in the first days of life. An intravenous fluid challenge allows differentiation of prerenal failure and intrinsic renal failure. All clinical conditions associated with hypovolemia, hypoxemia, and hypotension in the newborn infant may lead to renal insufficiency, the leading causes being perinatal anoxia-ischemia and sepsis. The initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
130
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 27 publications
(51 reference statements)
6
130
0
6
Order By: Relevance
“…These findings are consistent with the current knowledge that various clinical conditions occurring in NICU may impair neonatal renal function: Creatinine changes in preterm infants S Iacobelli et al RDS, mechanical ventilation, systemic hemodynamic compromise, acute anemia, dehydration, hypoxemia, acidosis and nephrotoxic drugs including ibuprofen. 22 We have also found that in infants with hsPDA, SeCr increase preceded ibuprofen administration, this suggesting that a renal impairment because of PDA and/or associated conditions exists before starting NSAID therapy. Concerning this point, many studies demonstrated that prophylactic or therapeutic ibuprofen, as with other cyclooxygenase inhibitors, may not be exempt from causing renal adverse effects, [23][24][25] but few investigations have explored the effect on renal function of PDA before and independently from ibuprofen treatment.…”
Section: Discussionmentioning
confidence: 54%
“…These findings are consistent with the current knowledge that various clinical conditions occurring in NICU may impair neonatal renal function: Creatinine changes in preterm infants S Iacobelli et al RDS, mechanical ventilation, systemic hemodynamic compromise, acute anemia, dehydration, hypoxemia, acidosis and nephrotoxic drugs including ibuprofen. 22 We have also found that in infants with hsPDA, SeCr increase preceded ibuprofen administration, this suggesting that a renal impairment because of PDA and/or associated conditions exists before starting NSAID therapy. Concerning this point, many studies demonstrated that prophylactic or therapeutic ibuprofen, as with other cyclooxygenase inhibitors, may not be exempt from causing renal adverse effects, [23][24][25] but few investigations have explored the effect on renal function of PDA before and independently from ibuprofen treatment.…”
Section: Discussionmentioning
confidence: 54%
“…The large extracorporeal circuit volumes, anticoagulation, and vascular access required are limiting factors, particularly in neonates. As a result, peritoneal dialysis (PD) is generally the most common form of RRT in young children, including neonates, the advantages being relative ease of access and technical simplicity (6,7). Acute PD can easily be performed in units with no HD expertise, and it is effective for the management of AKI and metabolic disturbances in children of all ages, including newborns and preterm infants (8).…”
mentioning
confidence: 99%
“…The reported incidence of neonatal AKI ranges from 6% to 24% (2,5). A recent, single-center study reported a 10-y incidence of renal failure in Ͻ1000 g infants of 5.5%.…”
mentioning
confidence: 99%